Thyroid Function in Korean Adolescents with Obesity: Results from the Korea National Health and Nutrition Examination Survey VI (2013–2015) - Won Kyoung Cho; Hyo-Kyoung Nam; Jae Hyun Kim; Young-Jun Rhie; Sochung Chung; Kee-Hyoung Lee; Byung-Kyu Suh (International Journal of Endocrinology)
Purpose. In this study, we investigated the status of thyroid function and its association with metabolic risk factors in Korean adolescents. Methods. Among 2679 subjects aged 10–19 years who participated in the Korea National Health and Nutrition Examination Survey VI (2013–2015), 1067 adolescents (M=559, F=508) with available data on free T4 (FT4) and thyroid-stimulating hormone (TSH) were included. Study participants were classified into normal weight [body mass index (BMI) below 85th percentile, 80.7%], overweight (85th ≤ BMI< 95th percentile, 8.7%), and obesity (BMI ≥ 95th percentile, 10.6%). Results. With increasing levels of BMI category, the means of TSH increased (2.73 ± 0.06, 2.77 ± 0.02, and 3.24 ± 0.22 mIU/L, P=0.031) and FT4 decreased (1.30 ± 0.01, 1.26 ± 0.02, and 1.25 ± 0.02 ng/mL, P=0.001). Positive linear associations were observed between TSH and BMI z-score (P=0.031), waist circumference (P=0.013), waist-height ratio (P=0.002), systolic blood pressure (P=0.001), total cholesterol (P=0.008), and triglyceride (P=0.002) after adjusting for age and sex. With per-unit increase in TSH, the odds ratios of having abdominal obesity (OR = 1.18, 95% CI, 1.01–1.38) and triglyceride ≥ 150 mg/dL (OR = 1.18, 95% CI, 1.04–1.34) were significantly increased after adjusting for age, sex, and BMI. Conclusions. In adolescents with obesity, TSH was higher and FT4 was lower than in adolescents with normal weight. Hyperthyrotropinemia was associated with abnormal metabolic risk factors including abdominal obesity and elevated triglyceride.